VD_FINDINFO 41/2017 vom 7. März 2016 - VD Tribunal cantonal (2016)
ADMISSION DE LA DEMANDE, RÉCUSATION, REQUÊTE DE MAINLEVÉE, DÉNONCIATION SPONTANÉE | 47 al. 1 let. a CPC (CH), 8a al. 3 CDPJ, 8b al. 4 CDPJ